Socialist government health policy reforms in Bolivia and Ecuador: The underrated potential of integrated care to tackle the social determinants of health - Herland Tejerina; Werner Soors; Pierre De Paepe; Edison Aguilar Santacruz; Marie-Christine Closon; Jean-Pierre Unger (Social Medicine Publication Group, 2009)
Background Selective vertical programs prevailed over comprehensive primary health care in Latin America. In Bolivia and Ecuador, socialist governments intend to redirect health policy. We outline both countries' health system's features after reform, explore their efforts to rebuild primary health care, identify and explain policy gaps, and offer considerations for improvement. Methods Qualitative document analysis. Findings Earlier reform left Bolivia's and Ecuador's population in bad health, with limited access to a fragmented health system. Today, both countries focus their policy on household and community-based promotion and prevention. The negative effects on access to care of decentralization, dual employment, vertical programming and targeting are largely left unattended. Neglecting care is understandable in the light of particular interpretations of social medicine and social determinants, international policy pressures, reliance on external funding and institutional inertia. Current policy choices preserve key elements of selective care and consolidate commodification. It might not improve health and worsen poverty. Interpretation Care can be considered as a social determinant on its own. Key to the accomplishment of primary care is an integrated application of family medicine, taking advantage of individual care as one of the ways to act on social determinants. It deserves a central place on the policy-makers' priority list, in Bolivia and Ecuador as elsewhere.